15 Ischaemic events in hypertrophic cardiomyopathy patients with and without atrial fibrillation: a systematic review and meta-analysis. (6th June 2022) - Siah, Qi Zhuang; Ye, Tiffany TS; Tan, Benjamin YQ; Ho, Jamie SY; Syn, Nicholas LX; Teo, Yao Hao; Teo, Yao Neng; Yip, James W; Yeo, Tiong-Cheng; Lin, Weiqin; Wong, Raymond CC; Chai, Ping; et al.
Abstract : Introduction/Objectives: Hypertrophic cardiomyopathy predisposes to acute cerebrovascular events including ischaemic stroke, transient ischaemic attack and systemic thromboembolism. Atrial fibrillation confers even higher risk. We aim to report the incidence of these complications and to investigate the impact of atrial fibrillation on the prognosis of patients with hypertrophic cardiomyopathy. Methods: A literature search was performed on PubMed, Scopus, Embase/ Ovid and Cochrane library from inception to 20th March 2021. We compared the incidence of ischaemic strokes, transient ischaemic attack, non-specified thromboembolism events and systemic thromboembolism in hypertrophic cardiomyopathy patients with or without atrial fibrillation. Non-specified thromboembolism events in our paper referred to thromboembolic events whereby their types were not specified in the studies. Meta-analysis was performed using StataSE 16 software, and heterogeneity was assessed using I 2 test. Results: A total of 713 studies were identified. Thirty-five articles with 42, 570 patients were included. The pooled incidence of stroke/ transient ischaemic attack was 7.45% (95% confidence interval [CI] 5.80–9.52, p<0.001) across 24 studies with a total of 37, 643 hypertrophic cardiomyopathy patients. Atrial fibrillation significantly increased the risk of total stroke/ transient ischaemic attack (Risk Ratio 3.26, 95% CI 1.75–6.08, p<0.001, I 2 = 76.0). The incidence of stroke/ transient ischaemic attack was 9.30% (95% CI 6.64–12.87, p=0.316) in the apical hypertrophic cardiomyopathy subgroup. Conclusions: Concomitant atrial fibrillation in hypertrophic cardiomyopathy increases the risk of thromboembolic events including ischaemic stroke and transient ischaemic attack. The apical subgroup shows a similar risk of acute cerebrovascular events as the overall hypertrophic cardiomyopathy population. Conflict of Interest: None